2006
DOI: 10.1111/j.1365-2788.2006.00812.x
|View full text |Cite
|
Sign up to set email alerts
|

An investigation into food preferences and the neural basis of food‐related incentive motivation in Prader–Willi syndrome

Abstract: It would appear that incentive motivation alone plays a less powerful role in individuals with PWS than in those without the syndrome. This is likely to be due to the overriding intrinsic drive to eat because of a lack of satiety in those with PWS, and the impact of this on activity in the incentive processing regions of the brain. Activity in such reward areas may not then function to guide behaviour selectively towards the consumption of high preference foods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 33 publications
2
31
0
2
Order By: Relevance
“…[681] failed to replicate this finding). In support of these findings, Shapira and colleagues [682] showed that in patients with PWS that there was a temporal delay in response to glucose ingestion in the resting-state activity of a distributed network implicated in the regulation of hunger and satiation, namely the hypothalamus, insular cortex, ventral basal ganglia, and ventromedial prefrontal cortex.…”
Section: Reviewmentioning
confidence: 95%
“…[681] failed to replicate this finding). In support of these findings, Shapira and colleagues [682] showed that in patients with PWS that there was a temporal delay in response to glucose ingestion in the resting-state activity of a distributed network implicated in the regulation of hunger and satiation, namely the hypothalamus, insular cortex, ventral basal ganglia, and ventromedial prefrontal cortex.…”
Section: Reviewmentioning
confidence: 95%
“…37 Studies have shown that people with PWS do discriminate and show preferences between foods. 40 PWS is associated with a high response on the 'ritualized eating behaviour item' from the Yale-Brown Obsessive Compulsive Scale (Y-BOCS 41 ), and people with PWS switch less between food types than mental-age matched controls on a standard meal. 42 This study also found that the bite rate correlated negatively with ordering non-food items into patterns.…”
Section: Behavioural Characteristics and Developmentmentioning
confidence: 99%
“…The disease incidence is 1: 10,000 to 30,000 births 1.2. The cognitive and behavioral phenotype observed in people with PWS is characterized by frequent episodes of hyperphagia, stealing food, tantrums, lying behavior, mood swings, anxiety, sadness, aggression and auto aggression, stubbornness and repetitive speech, hypersomnia, compulsive behaviors, deficits in cognitive abilities such as attention and executive functions (especially inhibitory control, working memory and self-regulation) and deficits in visuospatial skills [3][4][5][6][7] . Of these described characteristic phenotypes, the problems most difficult to manage are hyperphagia; stubborn behavioral patterns; challenging, aggressive, oppositional and manipulative behaviours; food theft and lying, which become more frequent and severe with increasing age [8][9][10][11] . Parents and caregivers of people with PWS are routinely faced with two types of problems; the control of access to food to avoid and/or minimize other health problems (such as obesity, scoliosis, and cardiovascular and endocrine illnesses) 12 , and family burden, especially on the primary caregiver, due to the difficulties in the management of behavioral problems that start from early childhood 13,14,15 .…”
Section: Introductionmentioning
confidence: 99%